BLS training: Standard vs Virtual reality BLS training - Lazić, Aleksandra; Milic, Sasa; Fiser, Zoran (Journal Resuscitatio Balcanica, 2020)
ABSTRACT Aim: European Resuscitation Council BLS Provider course has well determined aims, objectives and outcomes. New technologies offer new opportunities and new didactic equipment for providing BLS training. Serbian Resuscitation Councils BLS working group opened the question related to the methodology in conducting these courses with use of devices which provide virtual reality (VR). A pilot course program with the use of VR devices was settled and conducted during students teaching at Universities in Serbia. Methods: Prospective randomized manikin study. Students were randomly selected at registration and divided into two groups. Group I –standard ERC BLS course. Group II – BLS course with use of VR didactic device. Before and after the course all candidates were assessed with Cardiff scoring system related to CPR protocol and chest compression. Results: 250 medical students participated. Group I had 125 students in total. The Zoll AED Pro showed that the depth and frequency of compressions was good in 67, 04%. In this group candidate evaluation marks was 4, 35 at the scale 1 to 5 points. Group II – 125 students in total. The data showed 63, 16 % of compressions were satisfactory in aspects of depth and/or frequency and there evaluation marks was 4,65. Conclusion: Virtual reality contributed to the candidate’s sense of satisfaction but did not significantly change the outcome and results of the BLS training